2007
DOI: 10.1371/journal.pone.0000688
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-High Discrimination Y Chromosome Short Tandem Repeat Multiplex DNA Typing System

Abstract: In forensic casework, Y chromosome short tandem repeat markers (Y-STRs) are often used to identify a male donor DNA profile in the presence of excess quantities of female DNA, such as is found in many sexual assault investigations. Commercially available Y-STR multiplexes incorporating 12–17 loci are currently used in forensic casework (Promega's PowerPlex® Y and Applied Biosystems' AmpFlSTR® Yfiler®). Despite the robustness of these commercial multiplex Y-STR systems and the ability to discriminate two male i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…Ychromosome short tandem repeats (Y-STRs), on the other hand, mutate rapidly and are more suitable for reconstructing the phylogeny of relatively recent demographic events as well as for forensic casework and paternity testing [2,[4][5][6]. Recently, Y-STR data have been increasingly used to investigate the evolution, migration, and genetic diversity of modern human populations [2,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Ychromosome short tandem repeats (Y-STRs), on the other hand, mutate rapidly and are more suitable for reconstructing the phylogeny of relatively recent demographic events as well as for forensic casework and paternity testing [2,[4][5][6]. Recently, Y-STR data have been increasingly used to investigate the evolution, migration, and genetic diversity of modern human populations [2,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Mixed sample resolution based on Y-STR analysis in male/female mixed samples is relatively straightforward but its applicability in direct personal identification is limited [7]. In our previous study based on Y-chromosome sequence identification and Y-STR profiling we showed that salivary samples gained from females could be a useful source of forensic evidence in specific cases of sexual assaults in which the victim (female) was constrained to kissing by the perpetrator (male) [10].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, Y-chromosomal short tandem repeats (Y-STR) profiling is of great help, because it is possible to successfully profile the male Y-STR haplotype that could be used for identification of the perpetrator [4,5]. However, Y-STR profiling has insufficient discrimination power and is usually not widely used for individual identification [6], although a recent study focused on ultrahigh discrimination multiplex DNA typing based on Y-STR profiling showed its applicability for personal identification [7]. Satisfactory resolution is typical for widely used autosomal STR (a-STR) profiling kits.…”
Section: Introductionmentioning
confidence: 99%
“…It is because autosomal STRs allow the detection of minor components only if they account for more than 5% of the mixture, as the rule of thumb [7,8]. Sex-typing based on amelogenin is an integral part of most identifiler PCR multiplex kits widely used for gender determination and plays an important role in forensic casework and creating DNA database [9].…”
Section: Introductionmentioning
confidence: 99%